Evaluation of Revenue Volatility Risk in Financing Assets of Islamic Banks in Indonesia: Variance and Standard Deviation Approach - Taujiharrahman, Darma; Kismojo, Bambang; Puspita, Elsa; Kharmain, Muhammad Miftah (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: This study aims to measure the risk associated with the financing assets of Islamic banks in Indonesia by examining the volatility of income generated, both at the level of individual assets and within a portfolio context..Design/methodology: This research adopts a quantitative approach through descriptive statistical methods. The analysis utilizes variance and standard deviation formulas to process historical data obtained from the official statistics of Islamic banking in Indonesia over the period 2015-2024.Findings: The findings indicate that portfolio diversification can reduce risk levels in Islamic bank financing assets. However, a high degree of correlation among financing instruments suggests that the diversification strategy may not be fully effective. This highlights the importance of asset selection and correlation analysis in constructing resilient Islamic finance portfolios.Practical implications: Periodic and empirical risk assessments are crucial for evaluating strategic vision within a risk management framework. This study reveals that diversification practices in Islamic banks in Indonesia are executed by considering risk-return deviation, particularly through high musyarakah allocations with low deviation rates. Equity-based financing demonstrates a safer deviation rate than fixed-based financing such as murabahah, istishna, and ijarah thereby offering an alternative allocation to secure portfolios.Originality/Value: This study contributes to the literature by offering an empirical evaluation of income volatility risks in Islamic banking financing assets. It critically assesses the implementation of diversification strategies, providing insights into their effectiveness and alignment with the foundational goals of Sharia-based financial risk management.